(untitled) (Global Journal of Human-Social Science, 2013)
An ex-post facto research design was employed to determine the composite and relative correlation between financial well-being of poor salary demoralized private and public sector graduate employees in South South Nigeria and the sale or distribution of Asian and U S A brand of food supplements A purposive sampling technique was used to select 361 University College of Agriculture College of Education Polytechnic and Theological Seminary graduate employees These for each of these institutions were in the category of the unemployed self employed private sector employed and government employed The causal models were tested through data collected through five instruments Entrepreneurship Characteristics Self Rating Questionnaire ECSRQ the Common Business Practice Questionnaire CBPQ the Personality Trait Job Creation Questionnaire PTJCQ the Gender Role stereotype Job Creation Questionnaire GRJCQ and the Curriculum Outcome Work Behaviour Inventory COWBI